2017
DOI: 10.1136/oemed-2017-104575
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory disease in French nuclear fuel cycle workers chronically exposed to uranium: a nested case–control study

Abstract: Our results suggest that a positive association might exist between internal uranium exposure and CSD mortality, not confounded by CSD risk factors. Future work should focus on numerous uncertainties associated with internal uranium dose estimation and on understanding biological pathway of CSD after protracted low-dose internal radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…To date, only a few studies have examined risks of exposures in the uranium processing industry, (Dupree et al 1987;Dupree-Ellis et al 2000;Pinkerton et al 2004;Boice et al 2008;Guseva Canu et al 2010;Nusinovici et al 2010;Richardson et al 2013;Silver et al 2013;Zablotska et al 2013;Gillies and Haylock 2014;Kreuzer et al 2015;Zhivin et al 2016;Yiin et al 2017;Bouet, Samson, et al 2018;Yiin et al 2018;Zhivin et al 2018;Bouet, Davesne, et al 2019;Golden et al 2019) and even fewer conducted dose-response analyses of uranium processing workers with individual radiation doses (Dupree-Ellis et al 2000;Guseva Canu et al 2010;Silver et al 2013;Zablotska et al 2013;Gillies and Haylock 2014;Kreuzer et al 2015;Zhivin et al 2016;Yiin et al 2017;Yiin et al 2018;Zhivin et al 2018;Golden et al 2019). These studies reported contradictory results, necessitating further research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few studies have examined risks of exposures in the uranium processing industry, (Dupree et al 1987;Dupree-Ellis et al 2000;Pinkerton et al 2004;Boice et al 2008;Guseva Canu et al 2010;Nusinovici et al 2010;Richardson et al 2013;Silver et al 2013;Zablotska et al 2013;Gillies and Haylock 2014;Kreuzer et al 2015;Zhivin et al 2016;Yiin et al 2017;Bouet, Samson, et al 2018;Yiin et al 2018;Zhivin et al 2018;Bouet, Davesne, et al 2019;Golden et al 2019) and even fewer conducted dose-response analyses of uranium processing workers with individual radiation doses (Dupree-Ellis et al 2000;Guseva Canu et al 2010;Silver et al 2013;Zablotska et al 2013;Gillies and Haylock 2014;Kreuzer et al 2015;Zhivin et al 2016;Yiin et al 2017;Yiin et al 2018;Zhivin et al 2018;Golden et al 2019). These studies reported contradictory results, necessitating further research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…While a substantial body of epidemiologic literature on occupational cohorts exposed to ionizing radiation exists, few have directly estimated dose-response associations for internal exposure with individual doses. The majority of these studies reported increases, though often not statistically significant, in radiation risks of lung cancer among workers with exposures to processed uranium (Chan et al 2010;Boice et al 2011;Silver et al 2013;Zablotska et al 2013;Kreuzer et al 2015;Zhivin et al 2018;Golden et al 2019). While several studies reported increased risk of kidney cancer from RDP exposure, uranium or uranium/external exposures (Boice et al 2011;Silver et al 2013;Zablotska et al 2013;Yiin et al 2018;Golden et al 2019), many were not statistically significant due to low statistical power, primarily related to small numbers of kidney cancers.…”
Section: Discussionmentioning
confidence: 99%
“…uranium enrichment workers), and they should be carefully evaluated in separate studies. To date, only a few studies have conducted dose-response analyses of uranium processing workers with individual radiation doses (Dupree-Ellis et al 2000;Guseva Canu et al 2010;Silver et al 2013;Zablotska et al 2013;Gillies and Haylock 2014;Kreuzer et al 2015;Zablotska et al 2018;Zhivin et al 2018;Golden et al 2019). A limited number of these studies estimated individual doses from uranium or other radionuclides (Silver et al 2013;Kreuzer et al 2015;Zhivin et al 2018;Golden et al 2019), and study findings were constrained by relatively small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Such large amounts of data and of dose calculations require automation, whereas this is not the usual scenario for operational internal dose assessments in case of routine or special monitoring of exposed workers. Different programs were developed to derive annual absorbed doses for epidemiological studies: the Mayak Worker Dosimetry System-2013 for the Mayak cohort [47] , PuMA and IMBA for Sellafield workers [58] , InDep [48] for uranium enriched workers and DOSEPI for the TRACY cohort [46] .…”
Section: Differences Between Dose Evaluation For Radiation Protectionmentioning
confidence: 99%